Pengaruh pola asuh orang tua terhadap tingkat kemandirian toilet training pada anak usia prasekolah - Nanda, Febrika Devi; Sasongko, Hendrik Probo; Puspitasari, Lina Agustiana (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: The success of toilet training is not only seen from the child's physical readiness but also from the readiness of the parents, especially the mother, because toddlers still have physical, verbal and emotional limitations in carrying out toilet training. Purpose: To analyze the influence of parenting patterns on the level of toilet training independence in preschool-aged children. Method: Quantitative research with a cross-sectional approach, conducted in June-July 2024. The independent variable in this study is parenting patterns, while the dependent variable is the level of toilet training independence in preschool children. Sampling used the total sampling technique and obtained 60 respondents. Results: The parenting patterns of parents were mostly categorized as good as 38 respondents (63.3%) and the level of independence was categorized as high as 36 respondents (60.0%) with (p) (2-tailed) 0.01 which means there is an influence between the parenting pattern variable and the variable of children's toilet training independence. Conclusion: Parenting patterns have a significant influence on the level of toilet training independence in preschool children. Suggestion: Parents can apply democratic parenting in an effort to encourage healthy psychological growth and development of adolescents. Children's independence needs to be taught early on, children already have the drive to be independent for themselves, independence in each child cannot be the same. Keywords: Independence; Parenting Patterns; Preschool Age Children; Toilet Training. Pendahuluan: Keberhasilan toilet training tidak hanya dilihat dari kesiapan fisik anak, tetapi juga dilihat dari kesiapan orang tua, khususnya ibu karena usia toddler masih memiliki keterbatasan fisik, verbal, dan emosional dalam melakukan toilet training. Tujuan: Untuk menganalisis pengaruh pola asuh orang tua terhadap tingkat kemandirian toilet training pada anak usia prasekolah. Metode: Penelitian kuantitatif dengan pendekatan cross sectional, dilakukan pada bulan Juni-Juli 2024. Variabel independen pada penelitian ini adalah pola asuh orang tua, sedangkan variabel dependennya yaitu tingkat kemandirian toilet training pada anak usia prasekolah. Sampel dikumpulkan menggunkan teknik total sampling dan dapatkan sebanyak 60 responden. Hasil: Pola asuh orang tua sebagian besar masuk dalam kategori baik sebanyak 38 responden (63.3%), begitupun tingkat kemandirian dikategorikan tinggi sebanyak 36 responden (60.0%) dengan (p) (2-tailed) 0.01, artinya ada pengaruh antara variabel pola asuh dengan variabel kemandirian toilet training anak. Simpulan: Pola asuh orang tua berpengaruh secara signifikan terhadap tingkat kemandirian toilet training pada anak usia prasekolah. Saran: Orang tua dapat mempraktikkan pola asuh demokratis dalam upaya mendorong perkembangan psikologis remaja yang sehat. Kemandirian anak perlu diajarkan sejak dini, anak sudah mempunyai dorongan kemandirian untuk dirinya sendiri, kemandirian pada setiap anak tidak bisa disamakan. Kata Kunci: Anak Usia Prasekolah; Kemandirian; Pola Asuh Orang Tua; Toilet Training.